Treatment of coal-conversion wastewater with the powdered activated carbon-contact stabilization activated-sludge process. First semiannual technical progress report, August 1, 1980-January 31, 1981 - Suidan, M.T.; Pirbazari, M.; Gee, C.S.; Deady, M.A. (Illinois Univ., Urbana (USA). Dept. of Civil Engineering, 1981)
The treatment of coal conversion wastewaters has traditionally been accomplished through the use of the activated sludge process and its various modifications. General observations have been that phenol was degraded efficiently; however, very poor removal efficiencies of thiocyanate, cyanide, and ammonia were obtained. The addition of powdered activated carbon (PAC) to the activated sludge process has been reported to result in a number of distinct advantages. Generally, however, improving the effluent water quality beyond the capabilities of conventional biological treatment and enhancing the treatability of wastewaters that inhibit or toxify biological treatment systems are the primary objectives of utilizing PAC in secondary biological treatment. The focus of the present research project is to assess the effectiveness of the powdered activated carbon-contact stabilization activated sludge process in the treatment of a coking wastewater. The purpose of the contact tank in such a process will be to provide sufficient time for the adsorbable constituents of the coking wastewater to adsorb onto the PAC. The liquor leaving the contact tank is then clarified with the concentratrated underflow receiving treatment in the stabilization tank. After stabilization the sludge is returned to the contact tank. The clarifier supernatant is then nitrified in an activated sludge-type nitrification process and the nitrified effluent is subsequently denitrified in an anoxic filter.